2001
DOI: 10.1164/ajrccm.163.6.2005123
|View full text |Cite
|
Sign up to set email alerts
|

Quality-adjusted Survival in the First Year after the Acute Respiratory Distress Syndrome

Abstract: There is little information on long-term outcome after acute respiratory distress syndrome (ARDS). We measured quality-adjusted survival in the first year after ARDS in a prospective cohort (n = 200). All patients met traditional criteria for ARDS. Patients with sepsis and acute nonpulmonary organ dysfunction at presentation were excluded. The cohort was healthy before onset of ARDS as evidenced by high functional status (mean Karnofsky Performance Status index: 82.2/100 where >/= 80 = able to perform normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(189 citation statements)
references
References 35 publications
15
156
1
7
Order By: Relevance
“…However, in a single center, we have previously reported that survivors of PGD have worse pulmonary function and functional exercise capacity at 1 year (1, 5). Furthermore, nontransplant subjects who survive acute respiratory distress syndrome or sep- sis have greater mortality after hospital discharge (11,16,17), and survivors of acute respiratory distress syndrome have an increased risk of prolonged disability because of neuropathy, myopathy, malnutrition, and deconditioning (12). Thus, our findings may be attributable to the lingering effects after prolonged critical illness and the inability to withstand another illness.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in a single center, we have previously reported that survivors of PGD have worse pulmonary function and functional exercise capacity at 1 year (1, 5). Furthermore, nontransplant subjects who survive acute respiratory distress syndrome or sep- sis have greater mortality after hospital discharge (11,16,17), and survivors of acute respiratory distress syndrome have an increased risk of prolonged disability because of neuropathy, myopathy, malnutrition, and deconditioning (12). Thus, our findings may be attributable to the lingering effects after prolonged critical illness and the inability to withstand another illness.…”
Section: Discussionmentioning
confidence: 80%
“…In one study, it was suggested that severe ischemia-reperfusion injury increases the risk of chronic rejection and long-term mortality (9); however, others have found no such relationship (3). Furthermore, survivors of severe acute lung injury from a variety of other causes have increased mortality and impaired quality of life extending far beyond the initial hospitalization (10)(11)(12). Therefore, survivors of PGD could possibly have an increased risk of long-term mortality because of either chronic rejection or the after-effects of extended critical illness.…”
mentioning
confidence: 99%
“…Survivors of critical illness have been found to suffer from long-term sequelae, including increased long-term mortality [25], poor quality-adjusted survival [26], cognitive impairment and functional disability [27,28]. VOPs are not exempt from such adverse events, which often are perceived to occur beyond the scope of intensive care.…”
Section: Long-term Sequelaementioning
confidence: 99%
“…decreasing, the probability of mortality is considerably high and moreover this procedure results in a low quality-adjusted survival in the first year after ARDS [8,13] The continuous logic program for the extension of the predicate survival-rate: { ¬survival-rate(X, Y) ← not survival-rate(X, Y ) and not exception(survival-rate(X, Y)), exception(survival-rate(X, Y)) ← survival-rate(X, unknown-survival-rate), survival-rate(X, Y) ← ards(X) and pao2(X, low) and evaluate(X,Y), exception(survival-rate(gb, 0.5)), ? ((exception(survival-rate(X,Y)) or exception(survival-rate(X,Z))) and ¬(exception(survivalrate(X,Y)) and exception(survival-rate(X, Z))) /This invariant states that the exceptions to the predicate survival-rate follow an exclusive or/ }agsurvival-rate…”
Section: Case 1 Mr Pd Is a Man With 81 Years A Long Background Of Cmentioning
confidence: 99%